The residual repair capacity of xeroderma pigmentosum complementation group C fibroblasts is highly specific for transcriptionally active DNA. - Venema, J (1990)
We have measured removal of pyrimidine dimers in defined DNA sequences in confluent and actively growing normal human and xeroderma pigmentosum complementation group C (XP-C) fibroblasts exposed to 10 J/m2 UV-irradiation. In normal fibroblasts 45% and 90% of the dimers are removed from the transcriptionally active adenosine deaminase (ADA) gene within 4 and 24 hours after irradiation respectively. Equal repair efficiencies are found in fragments located entirely within the transcription unit or partly in the 3' flanking region of the ADA gene. The rate and extent of dimer removal from the dihydrofolate reductase (DHFR) gene is very similar to that of the ADA gene. Repair of the transcriptionally inactive 754 locus is less efficient: 18% and 52% of the dimers are removed within 4 and 24 hours respectively. In spite of the limited overall repair capacity, confluent XP-C fibroblasts efficiently remove dimers from the ADA and DHFR genes: about 90% and 50% within 24 hours respectively. The 3' end of the ADA gene is repaired as efficiently as in normal human fibroblasts, but less efficient repair occurs in DNA fragments located in the DHFR gene and at the 5' end of the ADA gene. Repair of the inactive 754 locus does not exceed the very slow rate of dimer removal from the genome overall. Confluent and actively growing XP-C cells show similar efficiencies of repair of the ADA, DHFR and 754 genes. Our findings suggest the existence of two independently operating pathways directed towards repair of pyrimidine dimers in either active or inactive chromatin. XP-C cells have lost the capacity to repair inactive chromatin, but are still able to repair active chromatin.